PENGEMBANGAN KBP DAN KEBERLANJUTAN HUTAN MANGROVE DI PATIMBAN, SUBANG, JAWA BARAT - Larasati, Sharfina Elda; Daulay, Rasoki Mintana Debara; Bashir, Imam Abdullah (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2024)
The focus of the development of the New City of Patimban(NCP) in Subang, West Java, lies in aligning with the city's aspirations and safeguarding the nearby mangrove forests. Guided by the West Java RTRW 2022-2042 and Subang Regent Regulation No. 38 of 2021, the development faces a challenge as allocating land for industrial purposes may adversely affect the mangrove ecosystems. Examining this situation through a Social-Ecological Systems (SES) lens reveals the need to comprehend the development's impact on mangrove forests.The research, titled